Pemanfaatan Buku Saku Kader Posyandu Kesehatan Gigi Mulut Ibu Hamil di Posyandu Peruri, Tangerang Selatan - Mutiara Rina Rahmawati Ruslan; Sarah Mersil; Lukas Kusparmanto; Muhamad Agung Nugroho; Anindya Syafara Mulyanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Dental and oral health problems in pregnant women are still an important issue in Indonesia. According to RISKESDAS 2018, the prevalence of dental caries reached 45.3% and gingivitis was 14%, with a higher prevalence in women (74%). Hormonal and behavioral changes during pregnancy increase the risk of dental and oral diseases, which can impact premature birth, preeclampsia, low birth weight (LBW), and stunting. The objective of this activity is to enhance the knowledge and skills of the Peruri Posyandu cadres in detecting dental and oral diseases in pregnant women through training that utilizes a pocketbook for dental and oral examination in pregnant women. The implementation method includes socialization, training, technology application, mentoring, and evaluation. The educational media used were educational posters, dental models, a pocketbook for oral cavity examination of pregnant women, and dental oral health examination cards for pregnant women. The results showed an 80% increase in cadres' knowledge and an 80% increase in their skill to detect dental cavities and other dental diseases. These findings indicate that the training is effective in equipping cadres with practical skills that can be applied in the field. The expected long-term impact includes increased awareness and improved behaviors of pregnant women regarding oral and dental health, as well as the strengthened role of Posyandu cadres in the early detection of oral diseases. The planned follow-up actions include ongoing mentoring, maintenance of educational media, and periodic evaluations to ensure the sustainability of the program.